Bio-inspired directional sensor with piezoelectric microfiber and helical electrodes. (August 2016) - Tao, Junliang; Yu, Xiong (Bill)
Inspired by the hair cells of vertebrates and aquatics, we proposed a hair sensor design that mimics the directionality and linearity of hair cells. The sensor promotes a novel use of piezoelectric microfiber with unique helical electrodes. The sensing mechanism was modeled both analytically and numerically. The analytical model explicitly illustrates the effects of the various design parameters on the performance of the sensor; the numerical model took into account the complex geometry of the sensor and elucidated the importance of the orientation of piezoelectric polarization on the piezoelectric effects. Both models provide valuable insight to optimize the sensor performance. Hair sensor prototypes were fabricated and characterized in the laboratory. The sensor output was found to be linearly dependent on the magnitude of applied displacements. Besides, at the same magnitude of deflection, the sensor responses followed a cosine function with the loading direction, which is similar to what is observed on the directionality of biological hair cells. These experimental observations were consistent with the results of model simulations. An algorithm was proposed to determine the magnitude and direction of acoustic stimuli by utilizing just a pair of orthogonally polarized and closely spaced hair cell sensors.